Southern limit of the Patagonian Ice Sheet - Hodgson, Dominic A.; Roberts, Stephen J.; Izagirre, Enaut; Perren, Bianca B.; De Vleeschouwer, Francois; Davies, Sarah J.; Bishop, Thomas; Mcculloch, Robert D.; Aravena Donaire, Juan Carlos (My University, 2023)
The southern limit of the Patagonian Ice Sheet at glacial maxima is poorly constrained due to a paucity of field data. This particularly applies to southern outlet glaciers of the Cordillera Darwin whose full extents have been debated by glacial geologists since 1899 CE, introducing uncertainty into estimates of total ice volume. Here we report on the stratigraphy of exposed stratigraphic sections on the west coast of Isla Hermite which include glacial diamict with discontinuous boulder pavement, overlain by successions of peats and sandy silt. The location of these sections, orientation of clasts within the glacial diamict, and geomorphology of the adjacent marine trough, suggest that an ice stream extended south from an ice centre at Cordillera Darwin across an extended Magellan outwash plain, through Paso Mantellero, to Islas Hermite and Cabo de Hornos (Cape Horn). This was similar in extent to the Canal Beagle and Lago Fagnano Ice Lobes which extended to the east. Retreat occurred sometime before 12,880 cal yr BP based on radiocarbon dated peat macrofossils immediately overlying the glacial diamict. We discuss whether this is a close minimum age, or a product of delayed onset of peat accumulation at the sampling site.
Keywords: quaternary; glaciation; south america; patagonia; geomorphology; last glacial maximum